2013
DOI: 10.1186/ar4240
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and Rho GTPase signaling in osteoarthritis development and intervention: implications for diagnosis and therapy

Abstract: Wnt and Rho GTPase signaling play critical roles in governing numerous aspects of cell physiology, and have been shown to be involved in endochondral ossification and osteoarthritis (OA) development. In this review, current studies of canonical Wnt signaling in OA development, together with the differential roles of Rho GTPases in chondrocyte maturation and OA pathology are critically summarized. Based on the current scientific literature together with our preliminary results, the strategy of targeting Wnt and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 92 publications
0
10
0
1
Order By: Relevance
“…While uncultured bacterium (77133) was observed to be involved in the upregulation of most of the ECM signaling and collagen pathways, the other microbes were significantly correlated to the downregulation of other signaling pathways crucial to joint and immune function. Wnt and Rho GTPase signaling pathways have a synergistic role in transducing signals from the ECM to govern numerous aspects of cell physiology and were both found to be downregulated [ 33 ]. In addition, the neutrophil degranulation pathway was also downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…While uncultured bacterium (77133) was observed to be involved in the upregulation of most of the ECM signaling and collagen pathways, the other microbes were significantly correlated to the downregulation of other signaling pathways crucial to joint and immune function. Wnt and Rho GTPase signaling pathways have a synergistic role in transducing signals from the ECM to govern numerous aspects of cell physiology and were both found to be downregulated [ 33 ]. In addition, the neutrophil degranulation pathway was also downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…PI3K/AKT-, MAPK-, WNT-, NTRK-, ERBB2-, and EGFR- signaling pathways were also overrepresented with key miR-375 target genes. However, PI3K/AKT-, MAPK- pathways are known to be significantly intermingled with Rho-GTPase signaling [ 7 , 8 ], whereas WNT-, NTRK-, ERBB2-, and EGFR-pathways may function via Rho-GTPase dependent transducers [ 9 , 10 , 11 , 12 , 13 ]. Thus, we may assume that miR-375 action in the heart muscle is primarily directed to the regulation of Rho-GTPase genes’ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1, a member of the Rho GTPase family, plays divergent roles in controlling cell cycle, cell–cell adhesion, motility (through controlling the actin network), and epithelial differentiation . Recent studies by our group and others have identified a key role of aberrant Rac1 activation in promoting chondrocyte hypertrophy and mineralization during OA development .…”
mentioning
confidence: 93%